Impact of Hybrid Working, Work-Life Balance, and Motivation on Job Satisfaction of Flip Employees - Ifan Fauzan Novyansyah; Fitria Yuliani (Universitas Bumigora, 2025)
Post-pandemic business slowdowns in the fintech sector, as experienced by PT Fliptech Lentera Inspirasi Pertiwi (Flip), have created an urgent need to maintain employee stability amidst changing work models. This study aims to analyze the determinants of job satisfaction by examining the influence of Hybrid Working, Work-Life Balance, and Motivation. The research employed a quantitative, causal design. Data were collected through questionnaires from 80 employees, determined using probability sampling with Slovin’s formula. The data were analyzed using multiple linear regression to test the partial and simultaneous effects of the variables. The findings demonstrate that Hybrid Working and Work-Life Balance have a positive and significant impact on Job Satisfaction, establishing flexibility as a primary driver of employee morale. Conversely, Motivation was found to have no significant impact on Job Satisfaction in this specific context. Simultaneously, the three variables significantly influence Job Satisfaction, explaining 26.1% of the variance. The study concludes that in a high-pressure fintech environment, employees prioritize autonomy and balance over generic motivational drivers. These find- ings offer practical implications for Flip’s management to prioritize and optimize hybrid work policies and